2020
DOI: 10.1177/0886260520976218
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With School Bullying Behaviors: A Chinese Adolescents Case-Control Study, 2019

Abstract: This research aimed to identify risk factors including individual characteristics and environment circumstances related to different types of school bullying (physical, relational, verbal, sexual, and possession bullying) among middle school students in China. Cases were the respondents reporting perpetrating bullying behaviors three or more times in the past year. One control was selected for each case from those participants who were not involved in school bullying in the past 12 months. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Aggression is a signi cant public health problem among adolescents, which hurts their physical and mental health. We found that the family APGAR index was negatively associated with aggressive behaviour which are consistent with previous study [29] .…”
Section: Discussionsupporting
confidence: 93%
“…Aggression is a signi cant public health problem among adolescents, which hurts their physical and mental health. We found that the family APGAR index was negatively associated with aggressive behaviour which are consistent with previous study [29] .…”
Section: Discussionsupporting
confidence: 93%
“…The power imbalance perceived or actually existing by *Corresponding author: Sultan Ayaz Alkaya, e-mail address: sultan@gazi.edu.tr 3 individuals is one of the most important causes of bullying (Olweus, 2012;Maïano, Aime, Salvas, Morin, & Normand, 2016;Smith, 2016). Age, gender, family and friend relationships are commonly identified as risk factors for peer bullying (Ayaz-Alkaya & Avşar, 2017;Zhang et al, 2019;Qian et al, 2022). Accordingly, it has been reported that boys are more involved in bullying than girls (Ayaz-Alkaya & Avşar, 2017;Zhang et al, 2019) and adolescents with poor family and friend relationships (Ayaz-Alkaya & Avşar, 2017;Qian et al, 2022).…”
Section: Peer Bullyingmentioning
confidence: 99%
“…Recently, bullying among school-aged children in China has become a severe problem [ 15 ]. The prevalence of self-reported school bullying in mainland China ranged from 2 percent to 34 percent [ 17 ]. It is important to examine school bullying in China.…”
Section: Introductionmentioning
confidence: 99%
“…Parental absence was more likely to increase the risk of child victimization and accidental injury [ 26 ]. On the other hand, LBC may lack empathy and become indifferent due to a lack of parental supervision and support [ 17 ]. However, Wen et al [ 27 ] found that parental migration might be not a risk factor for youth development in terms of at least character.…”
Section: Introductionmentioning
confidence: 99%